2D organic-α-Co(OH)2 material and derived Co/C composites with bifunctions of anti-corrosion and microwave absorption. (1st November 2021) - Ge, Jianwen; Cui, Yu; Cai, Yahui; Qian, Jiaxin; Liu, Li; Meng, Fandi; Wang, Fuhui
Abstract: In this article, α-Co(OH)2 lamellae as the precursor of ultimate Co/C composites was successfully fabricated utilizing glycol and Co 2+ under the solvothermal conditions, where the final detections of amorphous carbon, dispersed inner α-Co(OH)2 nanoparticles and related microstructures were investigated. After in situ polymerization and subsequent calcination, it is suggested that decorated carbon play an essential part in tuning the microstructure, where sample S1 with minimum additional carbon can be visualized the carbon skeleton which belonged to original α-Co(OH)2 precursors. Results of absorption properties exhibit that the most outstanding absorption performance corresponds to sample S1 with high intensity of −64.2 dB and broad EAB up to 6.7 GHz at 2.17 mm. Meanwhile, ring-shaped Co/C composites were generated at relatively low temperature (550 °C), and the optimal EAB reaches 6.5 GHz. Besides, sample S2 is endowed with the outstanding corrosion resistance for highest E corr (corrosion potential) and lowest I corr (corrosion current), which is derived from the protection of carbon layers. Considering the excellent corrosion resistance, wetting effect and microwave absorption characteristics, the new hybrids provide an opportunity for the design of absorbent with commercial value. Graphical abstract: Image 1 Highlights: Authors first reveal the microstructures and components of such 2D organic-α-Co(OH)2 composites. Different polymer contents and temperatures lead to various micromorphology of Co/C composites. The corrosion resistance of samples with different carbon content was measured.